20th century ghosts [compact disc, unabridged] - Hill, Joe (Harper Audio, 2007)
A compilation of short fiction includes the tales of Imogene, the legendary ghost of the Rosebud theater, and Francis, an unhappy, hopeless human turned giant locust seeking revenge on his Nevada hometown.